Structural, immunohistochemical and molecular features of placentas and placental sites after in vitro fertilization with donor eggs (surrogate motherhood). (July 2019) - Kogan, Еvgeniya А.; Rudenko, Ekaterina Е.; Demura, Tatiana А.; Zharkov, Nikolay V.; Trifonova, Natalia S.; Zhukova, Elvira V.; Aleksandrov, Leonid S.; Bayanova, Sofia N.
Abstract: Objective: to identify structural, immunohistochemical and molecular features of placentas and placental sites after in vitro fertilization (IVF) with donor eggs (surrogate motherhood). Study design: morphological and immunohistochemical studies were performed on placental material obtained after delivery by caesarean section. The study included 26 women patients whose pregnancy resulted from IVF with a donor egg (IVF-SM group). The comparison group included 13 women patients whose pregnancy occurred after IVF with their own eggs (IVF-OE). Immunohistochemistry of biopsy material was performed using mouse antibodies to total cytokeratin (clone AE1/AE3) and murine antibodies to HLA-DR (clone TAL.1B5). Molecular studies were performed on DNA samples isolated from venous blood. HLA-DNA-TEH reagent kits and polymerase chain reaction were used for genotyping the main human histocompatibility complex class II (DQA1, DQB1 and DRB1). Results: Histological examination of placenta in IVF-SM group showed a high incidence of central ischemic infarctions (69% of cases), dissociated cotyledon development (61%), pathological villus immaturity (46%) and massive perivillous fibrin deposition (73%). This group also had a pronounced lymphoplasmacytic deciduitis, which was 2 times higher than in the control group, and an expressed inflammatory process in the placental sites. Remodeling of the spiral arteries was incomplete in more than 40% of cases, and 30% of spiral arteries had no gestational changes. In comparison group, a complete gestational adjustment was found in more than 90% of spiral arteries. A focal lymphohistiocytic infiltration in perivascular regions, and a decrease in the number of multinucleated cells as compared with the control were also observed. For seven female surrogate mothers and their children, allelic polymorphisms of genes of HLA II class were studied. Conclusion: Placental material of women from IVF-SM group is characterized by complex immune response in sites of tight contact between maternal and fetal tissues. The immune pathogenesis is associated with an increase in the number of HLA-DR positive cells, defects in remodeling of the spiral arteries, development of areas of chronic inflammation in perivascular regions, and a decrease in the number of multinucleated cells. Genetic incompatibility between alleles of HLA II genes can be a molecular predictor of impaired immune tolerance.